Vulnerability of pejerrey Odontesthes bonariensis populations to climate change in pampean lakes of Argentina - Kopprio, Germán Adolfo (2010)
The vulnerability of the pejerrey Odontesthes bonariensis population in Lake Chasico was assessed ´ under different climate change conditions. During the sampling period, the water temperature was adequate for fish reproduction and to sustain an adequate sex ratio. Climate-driven higher temperatures, however, may severely distort population structure and cause drastic reduction or local extinction of stocks. Lake Chasico can be classified as eutrophic with clear waters and cyanobacte- ´ ria that regularly cause fish mortality were identified as Nodularia spumigena and Oscillatoria sp. Global warming may strengthen the effects of eutrophication (e.g. toxic blooms or anoxia). Since many Cyanophyta species tolerate higher temperatures better than other algae, toxic blooms could increase. Furthermore, cyanobacteria have low nutritional value and could decouple the low-diversity food web. Lake Chasico has currently the salinity optimum ( ´ c. 20) for the development of the early life-history stages of O. bonariensis. Climate change, however, is likely to amplify the intensity of droughts or inundations. Floods can endanger O. bonariensis development due to its sub-optimal growth at low salinity and droughts could increase lake salinity and also temperature and nutrient concentration. In order to reduce some of the effects of climate change on the O. bonariensis population in Lake Chasico, integrated basin management based on an eco-hydrological approach is ´ proposed.